Sosialisasi dan Pelatihan Pembuatan Kue Daun Kelor (Moringa Oleifera) - T, Ruslang; Sulaiman, Zulkarnain; Wahyuddin, Wahyuddin; Hasnaeni, Hasnaeni; Mutiah, Mutiah; Usman, Usman; Sari, Rasidah Wahyuni (Universitas Muhammadiyah Mataram, 2025)
Abstract: Kedai 'Aisyiyah is one of the businesses in Parepare City that still faces obstacles, especially in production and marketing. Kedai 'Aisyiyah's products do not yet have advantages and uniqueness, resulting in low competitiveness and a conventional marketing system. The goal of this program is to improve partners' knowledge and skills in making moringa leaf cakes, especially moringa leaf brownies and cookies. To address these issues, community service activities were carried out in the form of product innovation assistance through the use of local moringa leaf food and the application of smart oven technology. The program was implemented at the Culinary Laboratory of Muhammadiyah University of Parepare, involving 11 members of Kedai 'Aisyiyah. The implementation method included five stages: socialization, preparation, education on the nutritional content of moringa leaves, training in making moringa leaf cakes, and monitoring. The results of the activity showed a 55% increase in participants' knowledge, as evidenced by a comparison of pre-test and post-test results. In addition, partners' skills in producing moringa leaf cakes improved significantly after participating in the training.Abstrak: Kedai 'Aisyiyah merupakan salah satu usaha di Kota Parepare yang masih mengalami kendala khususnya dalam produksi dan pemasaran. Produk Kedai 'Aisyiyah belum memiliki keunggulan dan keunikan sehingga daya saingnya rendah serta sistem pemasaran masih dilakukan secara konvensional. Tujuan program ini adalah untuk meningkatkan pengetahuan dan keterampilan mitra dalam membuat kue daun kelor khususnya brownies dan cookies daun kelor. Untuk mengatasi permasalahan tersebut, dilakukan kegiatan pengabdian kepada masyarakat berupa pendampingan inovasi produk melalui pemanfaatan pangan lokal daun kelor dan penerapan teknologi smart oven. Program dilaksanakan di Laboratorium Kuliner Universitas Muhammadiyah Parepare dengan melibatkan 11 anggota Kedai ‘Aisyiyah. Metode pelaksanaan mencakup lima tahapan, yaitu sosialisasi, persiapan, edukasi kandungan gizi daun kelor, pelatihan pembuatan kue daun kelor, serta monitoring. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan peserta sebesar 55%, yang dibuktikan melalui perbandingan hasil pre-test dan post-test. Selain itu, keterampilan mitra dalam memproduksi kue daun kelor meningkat secara signifikan setelah mengikuti pelatihan.